Removal of Chloroacetanilide Herbicides from Water Using Heterogeneous Photocatalysis with TiO2/UV-A - Roulová, Nikola; Hrdá, Kateřina; Kašpar, Michal; Peroutková, Petra; Josefová, Dominika; Palarčík, Jiří (My University, 2022)
Chloroacetanilide herbicides are widely used in the agricultural sector throughout the world. Because of their poor biodegradability, high water solubility, and long persistence, chloroacetanilide herbicides have a high potential to contaminate water, and conventional water treatment processes do not ensure sufficient removal. Therefore, heterogeneous photocatalysis using TiO2/UVA was investigated for the degradation of alachlor, acetochlor, and metolachlor from water. Two commercially available TiO2 (P25 and AV-01) were used as photocatalysts. Different experimental setups were also tested. In addition, the toxicity of single herbicides and mixtures of their photocatalytic degradation products to the freshwater alga Chlorella kessleri was investigated via a growth inhibition test. The maximum removal efficiency for alachlor, acetochlor, and metolachlor was 97.5%, 93.1%, and 98.2%, respectively. No significant differences in the removal efficiency of chloroacetanilide herbicides were observed for the photocatalysts used. Although the concentrations of all herbicides during photocatalysis decreased, the toxicity of the resulting mixtures of degradation products increased or remained the same, indicating the formation of toxic degradation products.
Odstraňování chloracetanilidových herbicidů z vody pomocí heterogenní fotokatalýzy s TiO2/UV-A
Keywords: algal growth inhibition test; Chlorella kessleri; chloroacetanilide herbicides; heterogeneous photocatalysis; photocatalytic degradation; titanium dioxide; UV-A LED; test inhibice růstu řas; Chlorella kessleri; chloracetanilidové herbicidy; heterogenní fotokatalýza; fotokatalytická degradace; oxid titaničitý; UV-A LED